2011
DOI: 10.1021/ac2016932
|View full text |Cite
|
Sign up to set email alerts
|

TOFSIMS-P: A Web-Based Platform for Analysis of Large-Scale TOF-SIMS Data

Abstract: Time-of-flight secondary ion mass spectrometry (TOF-SIMS) has been a useful tool to profile secondary ions from the near surface region of specimens with its high molecular specificity and submicrometer spatial resolution. However, the TOF-SIMS analysis of even a moderately large size of samples has been hampered due to the lack of tools for automatically analyzing the huge amount of TOF-SIMS data. Here, we present a computational platform to automatically identify and align peaks, find discriminatory ions, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…This complicates or even makes impossible the precise identification of the original molecule that gave rise to the corresponding secondary ion. For example, it was previously shown that an ion with a mass of 127.04 can arise during ionization of at least five different metabolites and may have a different chemical structure (43). To overcome this issue, we used two complementary approaches.…”
Section: Discussionmentioning
confidence: 99%
“…This complicates or even makes impossible the precise identification of the original molecule that gave rise to the corresponding secondary ion. For example, it was previously shown that an ion with a mass of 127.04 can arise during ionization of at least five different metabolites and may have a different chemical structure (43). To overcome this issue, we used two complementary approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Using some analytical methods (eg stochastic optical reconstruction microscopy and cryo‐electron microscopy), there have been concomitant improvements in data analysis and visualisation methods . Time‐of‐flight secondary ion mass spectrometry is moving from small peak lists to those containing hundreds to thousands of peaks, in turn generating extensive data matrices spanning thousands to millions of potential data points . However, the ToF‐SIMS community still largely deals with informatics issues using relatively simple statistical methods like principal component analysis (PCA).…”
Section: Introductionmentioning
confidence: 99%
“…[8] Also, signal enhancements were observed in the high mass range when an argon cluster ion beam, rather than a bismuth ion beam, was used. [9][10][11] In this work, we analyzed Ap 3 A and Ap 4 A molecules spiked in HeLa cell lysates by using the ToF-SIMS technique. We will show that ToF-SIMS can be a useful technique to analyze metabolites such as Ap 3 A and Ap 4 A in cell lysates by using bismuth and argon cluster ion beams.…”
Section: Introductionmentioning
confidence: 99%